Perovskite battery and preparation method thereof

By using post-treatment solution and multiple spin-coating annealing treatment methods in perovskite batteries, the problem that it is difficult to deeply regulate perovskites in one-step solvent method is solved, and the photoelectric conversion efficiency and overall performance of the battery are significantly improved.

CN119730661APending Publication Date: 2025-03-28旗滨新能源发展(深圳)有限责任公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411618916.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The one-step solvent method is used to prepare the perovskite interface layer and it is difficult to deeply regulate and optimize the perovskite, resulting in low photoelectric conversion efficiency of the battery.

Method used

The post-treatment solution includes A-position small molecules, A-position macro molecules and energy-level modification molecules, and the interface modification layer is prepared by at least two spin coating and annealing treatments to deeply regulate the energy level and structure of the perovskite surface.

Benefits of technology

The photoelectric conversion efficiency, filling factor and open circuit voltage of perovskite batteries have been significantly improved, and the carrier extraction capability and overall performance of the battery have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730661A_ABST
    Figure CN119730661A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite battery and a preparation method thereof, and belongs to the technical field of perovskite batteries. The method comprises the following steps: dropwise adding a post-treatment solution to the surface of a perovskite light absorption layer, carrying out at least two times of spin coating treatment, and carrying out annealing treatment after each time of spin coating to obtain an interface modification layer; the post-treatment solution comprises A-site micromolecules, A-site macromolecules and energy level modification molecules. Therefore, not only can the perovskite light absorption layer be passivated and the perovskite chemical composition and crystal structure stability be maintained, but also the energy level of the perovskite surface can be modified, the charge recombination can be reduced, and the electron transmission capability can be improved. Besides, the interface modification layer is prepared through a post-treatment method for more than two times, so that the action depth of functional molecules is deepened, the gradually-rising gradient change of the functional molecules from a perovskite body phase to the surface is realized, the extraction of current carriers is facilitated, and the efficiency of the perovskite battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and in particular to a perovskite cell and a preparation method thereof. Background Art

[0002] Trans-perovskite materials have been widely used in the field of solar cells due to their excellent optoelectronic properties and cost-effectiveness. However, compared with the bulk perovskite phase, the surface of perovskite materials often has defects, interface energy level mismatch, slow carrier extraction and other problems, which will reduce the photoelectric conversion efficiency of the battery. Preparing an interface modification layer on the surface of perovskite is a common method to improve device performance, but the one-step solvent method to prepare the perovskite interface layer has a relatively shallow effect on the perovskite, and cannot deeply regulate and optimize the perovskite, and the performance improvement is limited. Summary of the invention

[0003] The main purpose of the present invention is to provide a perovskite battery and a preparation method thereof, so as to solve the technical problem that it is difficult to deeply regulate and optimize the perovskite interface layer in the one-step solvent method.

[0004] To achieve the above object, the present invention provides a method for preparing a perovskite battery, comprising the following steps:

[0005] The post-treatment solution is added dropwise onto the surface of the perovskite light-absorbing layer, and a spin coating process is performed at least twice, and an annealing process is performed after each spin coating process to obtain an interface modification layer;

[0006] The post-treatment solution includes A-site small molecules, A-site macromolecules and energy level modification molecules;

[0007] The A-site small molecule includes MA + , FA + ,DMA + At least one of the following;

[0008] The A-position macromolecule includes an aromatic amine halide salt;

[0009] The energy level modifying molecules include diamine halide salts.

[0010] In some embodiments of the present invention, the aromatic hydrocarbon amine halide salt includes phenylethylamine hydroiodide; and / or, the diamine halide salt includes piperazine hydroiodide.

[0011] In some embodiments of the present invention, the molar concentration of small molecules at site A in the post-treatment solution is 0.01M to 0.1M; and / or, the molar concentration of macromolecules at site A in the post-treatment solution is 0.01M to 0.1M; and / or, the molar concentration of energy level modification molecules in the post-treatment solution is 0.01M to 0.1M.

[0012] In some embodiments of the present invention, in the post-treatment solution, the molar ratio of the A-site small molecule, the A-site macromolecule and the energy level modification molecule is (1:1:0.1) to (1:1:0.6).

[0013] In some embodiments of the present invention, the post-treatment solution includes an organic solvent, and the organic solvent includes isopropanol.

[0014] In some embodiments of the present invention, the rotation speed of the spin coating is 2500 rpm to 3500 rpm; and / or the time of the spin coating is 25s to 35s.

[0015] In some embodiments of the present invention, the temperature of the annealing treatment is 95° C. to 105° C.; and / or the time of the annealing treatment is 9 min to 11 min.

[0016] In some embodiments of the present invention, the thickness of the interface modification layer is 0.1 nm to 3 nm.

[0017] In some embodiments of the present invention, the method for preparing the perovskite battery comprises the following steps:

[0018] One spin coating annealing: dripping the post-treatment solution onto the surface of the perovskite light absorbing layer, performing a spin coating process, and performing an annealing process to obtain an initial interface modification layer;

[0019] Secondary spin coating annealing: dripping the post-treatment solution onto the surface of the initial interface modification layer, performing secondary spin coating treatment, and performing secondary annealing treatment to obtain the interface modification layer.

[0020] The present invention also provides a perovskite battery prepared by the above-mentioned method for preparing the perovskite battery.

[0021] In some embodiments of the present invention, the perovskite cell comprises, from bottom to top, a transparent electrode, a hole transport layer, a perovskite light absorbing layer, the interface modification layer, an electron transport layer and a metal electrode.

[0022] The beneficial effects that can be achieved by the present invention are:

[0023] The post-treatment solution of the present invention comprises A-site small molecules, A-site macromolecules and energy level modification molecules. The A-site small molecules can supplement cations, and are used to supplement A-site cations such as formamidinium ions that may be lost during the flushing process of the post-treatment solution, so as to maintain the chemical composition and crystal structure stability of the perovskite. The A-site macromolecule plays a role in constructing a low-dimensional structure, constructing a low-dimensional structure on the surface of the perovskite, effectively passivating defects on the surface and grain boundaries of the perovskite material, thereby reducing charge recombination and improving the filling factor and photoelectric conversion efficiency of the battery. The energy level modification molecules can be used to modify the energy level of the perovskite surface, form an n-type surface, enhance the electron transmission ability of the perovskite material and reduce charge recombination, and further improve the open circuit voltage and overall performance of the perovskite battery.

[0024] The present invention also cooperates with at least two spin coating processes, and annealing treatment is performed after each spin coating to prepare an interface modification layer, which deepens the action depth of the material in the post-treatment solution in the perovskite light-absorbing layer, increases the concentration of energy level regulation molecules on the surface of the perovskite, and realizes a gradual increase in the gradient change of functional molecules from the perovskite bulk phase to the surface, forming a gradient energy level structure that is beneficial to carrier extraction, thereby improving the extraction of carriers and significantly improving the efficiency of perovskite batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0026] Figure 1 Schematic diagram of the structure of a perovskite battery according to an embodiment of the present invention.

[0027] Figure 2 Schematic diagram of the structure of a perovskite battery according to another embodiment of the present invention.

[0028] Figure 3 It is a comparison diagram of the current density-voltage (JV) curves of the perovskite batteries of Example 1, control group 1, and blank group 1 of the present invention.

[0029] Figure 4 It is a comparison diagram of the current density-voltage (JV) curves of Comparative Examples 1 to 6 of the present invention.

[0030] Figure 5 This is a comparison chart of the maximum power point output curves of the perovskite batteries of Example 1, control group 1, and blank group 1 of the present invention.

[0031] Figure 6It is a comparison diagram of the current density-voltage (JV) curves of the perovskite batteries of Example 2 of the present invention, the control group 2, and the blank group 2.

[0032] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings.

[0033] Description of Figure Numbers:

[0034] 1. Transparent electrode; 2. Hole transport layer; 3. Perovskite light absorption layer; 4. Interface modification layer; 5. Electron transport layer; 6. Hole blocking layer; 7. Metal electrode. DETAILED DESCRIPTION

[0035] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0038] The present invention provides a method for preparing a perovskite battery, comprising the following steps:

[0039] The post-treatment solution is added dropwise onto the surface of the perovskite light-absorbing layer, and a spin coating process is performed at least twice, and an annealing process is performed after each spin coating process to obtain an interface modification layer;

[0040] The post-treatment solution includes A-site small molecules, A-site macromolecules and energy level modification molecules;

[0041] The A-site small molecule includes MA + , FA + ,DMA + At least one of the following;

[0042] The A-position macromolecule includes an aromatic amine halide salt;

[0043] The energy level modifying molecules include diamine halide salts.

[0044] In the related technologies for post-processing the surface of the perovskite light-absorbing layer, traditional post-processing methods often only improve a single problem. For example, only a low-dimensional structure is formed on the surface of the perovskite light-absorbing layer to improve stability. However, the construction of the low-dimensional structure will inhibit the extraction of carriers. For another example, only the surface energy level is modified on the perovskite light-absorbing layer to improve the extraction of carriers, but this is difficult to inhibit ion migration. Moreover, the post-treatment solution usually dissolves the organic cations on the surface of the perovskite light-absorbing layer, destroying the balance of the perovskite components and reducing its stability.

[0045] The post-treatment solution of the present invention includes A-site small molecules, A-site macromolecules and energy level modification molecules, A-site small molecules can supplement cations, which are used to supplement A-site cations such as formamidinium ions that may be dissolved by the post-treatment solution, and play a role in maintaining the chemical composition and crystalline structure stability of perovskite; A-site macromolecules play a role in constructing low-dimensional structures, constructing low-dimensional structures on the surface of perovskite, effectively passivating defects on the surface and grain boundaries of perovskite materials, thereby reducing charge recombination and improving the filling factor and photoelectric conversion efficiency of the battery; and energy level modification molecules can be used to modify the energy level of the perovskite surface, forming an n-type surface, enhancing the electron transport capacity of the perovskite material and reducing charge recombination, and further improving the open circuit voltage and overall performance of the perovskite battery. Therefore, the post-treatment solution of the present invention relatively comprehensively modifies the perovskite light absorption layer, and improves the stability and device performance of the perovskite device.

[0046] In some embodiments, the A-site small molecule includes MA + , FA + ,DMA + At least one of them can contain MA + , FA + or DMA + The material is added to the post-treatment solution, for example, to provide MA + The materials include methyl ammonium chloride, which provides FA + Materials include formamidine hydrochloride, provided by DMA + The material includes dimethylamine hydrochloride.

[0047] In some embodiments, the A-site macromolecule comprises an aromatic amine halide salt, and the aromatic amine halide salt comprises phenylethylamine hydroiodide.

[0048] In some embodiments, the energy level modifying molecule diamine halide salt comprises piperazine hydroiodide.

[0049] In some embodiments, the molar concentration of the A-site small molecule in the post-treatment solution is 0.01M to 0.1M.

[0050] In some embodiments, the molar concentration of the A-site macromolecule in the post-treatment solution is 0.01M to 0.1M.

[0051] In some embodiments, the molar concentration of the energy level modifying molecule in the post-treatment solution is 0.01M to 0.1M.

[0052] In some embodiments, the molar ratio of the A-site small molecule, the A-site macromolecule and the energy level modifying molecule is (1:1:0.1) to (1:1:0.6). For example, it can be any ratio in the range of (1:1:0.1) to (1:1:0.6), such as 1:1:0.1, 1:1:0.2, 1:1:0.3, 1:1:0.4, 1:1:0.5, 1:1:0.6, etc.

[0053] In some embodiments, the post-treatment solution contains an organic solvent, which can be used to dissolve the materials providing the A-site small molecule, the A-site macromolecule and the energy level modification molecule to prepare the post-treatment solution.

[0054] In some embodiments, the organic solvent includes isopropyl alcohol.

[0055] In some embodiments, the A-site small molecule, the A-site macromolecule and the energy level modification molecule can be dissolved in organic solvents respectively to prepare the A-site small molecule solution, the A-site macromolecule solution and the energy level modification molecule solution, and then the A-site small molecule solution, the A-site macromolecule solution and the energy level modification molecule solution are mixed to obtain a post-treatment solution, so that the molar ratio of various molecules in the post-treatment solution can be controlled by controlling the volume ratio.

[0056] In the present invention, the interface modification layer is prepared by a two-post-treatment method of at least two spin coating processes, and annealing is performed after each spin coating process, so that the modification effect of various functional molecules in the post-treatment solution on the perovskite light-absorbing layer can be better exerted. It is understandable that the spin coating process can be performed more than twice, such as three times and four times, and annealing is performed after each spin coating process. After each spin coating and annealing process is completed, the next spin coating and annealing process is performed after cooling, which can be natural cooling.

[0057] In some embodiments, the rotation speed of the spin coating is 2500 rpm to 3500 rpm, and can be any value in the range of 2500 rpm to 3500 rpm, such as 2500 rpm, 3000 rpm, 3500 rpm, etc. It is understood that in this embodiment, the rotation speed of each spin coating is within the range of 2500 rpm to 3500 rpm, but it is not required that the rotation speed of each spin coating is the same.

[0058] In some embodiments, the spin coating time is 25s to 35s, and can be any value within the range of 25s to 35s, such as 25s, 28s, 30s, 33s, 35s, etc. It is understood that in this embodiment, the spin coating time is within the range of 25s to 35s, but it is not required that the spin coating time is the same each time.

[0059] In some embodiments, the temperature of the annealing treatment is 95° C. to 105° C., and can be any value in the range of 95° C. to 105° C., such as 95° C., 100° C., 105° C., etc. It can be understood that in this embodiment, the temperature of each annealing treatment is in the range of 95° C. to 105° C., but it is not required that the temperature of each annealing treatment is the same.

[0060] In some embodiments, the annealing time is 9 minutes to 11 minutes, and can be any value in the range of 9 minutes to 11 minutes, such as 9 minutes, 10 minutes, 11 minutes, etc. It can be understood that in this embodiment, the annealing time of each time is in the range of 9 minutes to 11 minutes, but it is not required that the annealing time of each time is the same.

[0061] In some embodiments, the thickness of the interface modification layer is 0.1 nm to 3 nm, such as any value in the range of 0.1 nm to 3 nm, such as 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, etc. The thickness of the interface modification layer can be controlled by controlling the process parameters of each spin coating annealing.

[0062] In some embodiments, when preparing the perovskite interface modification layer, a secondary spin coating process and a secondary annealing process are performed. Specifically, the preparation method of the perovskite battery in this embodiment includes the following steps:

[0063] One spin coating annealing: dripping the post-treatment solution onto the surface of the perovskite light absorbing layer, performing a spin coating process, and performing an annealing process to obtain an initial interface modification layer;

[0064] Secondary spin coating annealing: the post-treatment solution is dripped onto the surface of the initial interface modification layer, a secondary spin coating treatment is performed, and a secondary annealing treatment is performed to obtain the interface modification layer.

[0065] In this embodiment, the present invention prepares an interface modification layer by combining a post-treatment solution with a two-time post-treatment method, thereby deepening the action depth of the material in the post-treatment solution in the perovskite light-absorbing layer, increasing the concentration of energy level regulation molecules on the surface of the perovskite, and realizing a gradual upward gradient change of functional molecules from the perovskite bulk phase to the surface. It also realizes a gradient energy level structure that is beneficial to carrier extraction, thereby improving the extraction of carriers and significantly improving the efficiency of perovskite batteries.

[0066] In some embodiments, the rotation speed of a spin coating process is 2500 rpm to 3500 rpm, and can be any value within the range of 2500 rpm to 3500 rpm, such as 2500 rpm, 3000 rpm, or 3500 rpm.

[0067] In some embodiments, the temperature of the primary annealing treatment is 95°C to 105°C, and can be any value within the range of 95°C to 105°C, such as 95°C, 100°C, or 105°C.

[0068] In some embodiments, the rotation speed of the secondary spin coating process is 2500 rpm to 3500 rpm, and can be any value within the range of 2500 rpm to 3500 rpm, such as 2500 rpm, 3000 rpm, or 3500 rpm.

[0069] In some embodiments, the temperature of the secondary annealing treatment is 95°C to 105°C, and can be any value within the range of 95°C to 105°C, such as 95°C, 100°C, or 105°C.

[0070] In some embodiments, after completing a spin coating annealing, a second spin coating annealing is performed after cooling, which is beneficial to obtaining a complete interface modification layer with uniform composition. The cooling method can be natural cooling.

[0071] The perovskite battery of the present invention includes an inverted perovskite battery, referring to Figure 1 The perovskite cell includes, from bottom to top, a transparent electrode 1, a hole transport layer 2, a perovskite light absorption layer 3, an interface modification layer 4, an electron transport layer 5 and a metal electrode 7.

[0072] In some embodiments, reference Figure 2 The perovskite battery also includes a hole blocking layer 6, which is arranged between the electron transport layer 5 and the metal electrode 7, and can inhibit ion migration and improve electron transport efficiency, thereby achieving the purpose of improving device performance.

[0073] In the present invention, the materials and preparation methods used for other functional layers in the perovskite battery, such as the transparent electrode 1, the hole transport layer 2, the perovskite light absorbing layer 3, the electron transport layer 5 and the metal electrode 7, can refer to conventional methods in the art.

[0074] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0075] Example 1

[0076] The preparation method of the perovskite cell of Example 1 is as follows:

[0077] Step 1: Use 2.5 cm*2.5 cm ITO with an etched pattern as a transparent electrode, clean the transparent electrode ITO with a cleaning agent, acetone, and isopropyl alcohol in sequence, and then place it in a UV ozone treatment machine for 20 minutes to remove organic residues on the surface of the substrate.

[0078] Step 2, preparation of hole transport layer: nano nickel oxide powder with a particle size of 5nm to 10nm is dispersed in deionized water to obtain a nano nickel oxide solution with a concentration of 5mg / ml, the nickel oxide solution is filtered and spin-coated on the transparent electrode treated with ultraviolet ozone, and the nickel oxide film is spin-coated at a speed of 3000rpm for 30s to form a nickel oxide film, and then the spin-coated nickel oxide film is transferred to a glove box, and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) is dispersed A [2-(9H-carbazole-9-yl)ethyl]phosphonic acid solution with a concentration of 0.5 mg / mL was prepared in anhydrous ethanol, and the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid solution was spin-coated onto the surface of the nickel oxide film to form a [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) layer. The spin-coating conditions were as follows: a rotation speed of 3000 rpm and a time of 30 s. After spin coating, the film was annealed at 100°C for 10 min to complete the preparation of the hole transport layer.

[0079] Step 3: Prepare the perovskite light-absorbing layer: prepare 1.5M Cs 0.05 FA 0.85 MA 0.1 PbI3 was dissolved in a mixed solvent of DMF and DMSO to obtain a perovskite precursor solution, the volume ratio of DMF and DMSO was 4:1, and 8 mg of MACl and 51 mg of PbI2 were additionally added to each milliliter of perovskite precursor solution. The perovskite precursor solution was then filtered, and the filtered perovskite precursor solution was dropped onto the surface of the hole transport layer, first spin coated at 2000 rpm for 10 s, then spin coated at 4000 rpm for 40 s, and finally spin coated at 6000 rpm for 5 s. In the last 15 s, 150 uL of anisole was added as a poor solvent to promote perovskite crystallization. After spin coating, the perovskite light absorbing layer was annealed at 100 °C for 10 min to obtain the perovskite light absorbing layer.

[0080] Step 4, preparing an interface modification layer: dissolving formamidine hydrochloride (FACl), phenethylamine hydroiodide (PEAI), and piperazine hydroiodide (PI) in isopropanol solvent, respectively, with a concentration of 1 mg / mL. After sufficient stirring, filtering to obtain formamidine hydrochloride solution, phenethylamine hydroiodide solution, and piperazine hydroiodide solution, respectively, mixing the three solutions of FACl:PEAI:PI in a molar ratio of 1:1:0.1 to obtain a post-treatment solution, dropping the post-treatment solution onto the surface of the perovskite light-absorbing layer, and performing a spin coating treatment once, the rotation speed of the spin coating treatment is 3000 rpm, the time is 30 s, and then performing an annealing treatment at 100°C for 10 min to form an initial interface modification layer, and after natural cooling, the post-treatment solution is again dropped onto the surface of the initial interface modification layer, and a second spin coating treatment is performed, the rotation speed of the second spin coating is 3000 rpm, the time is 30 s, and then a second annealing treatment is performed at 100°C for 10 min to form an interface modification layer.

[0081] Step 5: Prepare C on the surface of the interface modification layer by thermal evaporation 60 Electron transport layer, thickness is 25nm.

[0082] Step 6: Prepare a bathcopperene hole blocking layer on the surface of the electron transport layer by thermal evaporation, with a thickness of 7 nm.

[0083] Step 7: Prepare a silver metal electrode on the surface of the copper bath hole blocking layer by thermal evaporation method, with a thickness of 120 nm.

[0084] Control group 1

[0085] The control group prepared a perovskite battery by referring to the preparation method of Example 1, except that when the control group 1 prepared the interface modification layer in step 4, only one spin coating and one annealing treatment were performed to obtain the interface modification layer, and no subsequent secondary spin coating and secondary annealing treatment were performed.

[0086] Blank group 1

[0087] The blank group prepared the perovskite battery by referring to the preparation method of Example 1, except that the blank group did not perform step 4 of preparing the interface modification layer.

[0088] Comparative Example 1

[0089] Comparative Example 1 A perovskite light absorbing layer was prepared by referring to the method of Example 1, except that the three solutions of FACl:PEAI:PI were mixed in a molar ratio of 1:0:0 to obtain a post-treatment solution.

[0090] Comparative Example 2

[0091] Comparative Example 2: A perovskite light absorbing layer was prepared by referring to the method of Example 1, except that the three solutions of FACl:PEAI:PI were mixed in a molar ratio of 0:1:0 to obtain a post-treatment solution.

[0092] Comparative Example 3

[0093] Comparative Example 3: A perovskite light absorbing layer was prepared by referring to the method of Example 1, except that the three solutions of FACl:PEAI:PI were mixed in a molar ratio of 0:0:1 to obtain a post-treatment solution.

[0094] Comparative Example 4

[0095] Comparative Example 4 A perovskite light absorbing layer was prepared by referring to the method of Example 1, except that the three solutions of FACl:PEAI:PI were mixed in a molar ratio of 1:1:0 to obtain a post-treatment solution.

[0096] Comparative Example 5

[0097] Comparative Example 5 A perovskite light absorbing layer was prepared by referring to the method of Example 1, except that the three solutions of FACl:PEAI:PI were mixed in a molar ratio of 1:0:0.1 to obtain a post-treatment solution.

[0098] Comparative Example 6

[0099] Comparative Example 6: A perovskite light absorbing layer was prepared by referring to the method of Example 1, except that the three solutions of FACl:PEAI:PI were mixed in a molar ratio of 0:1:0.1 to obtain a post-treatment solution.

[0100] Example 2

[0101] The preparation method of the perovskite solar cell of Example 2 is as follows:

[0102] Step 1: Use 10cm*10cm ITO as a transparent electrode and divide it by laser scribing. This step is called P1. The line width of P1 is 40um. Then, the transparent electrode ITO is cleaned with a cleaning agent, acetone, and isopropyl alcohol in turn, and then placed in a UV ozone treatment machine for 20 minutes to remove organic residues on the surface of the substrate.

[0103] Step 2 is consistent with Step 2 in Example 1.

[0104] Step 3, preparation of perovskite layer: prepare a perovskite precursor solution with a concentration of 1.4M FAPbI3, and then add 10mg MACl per milliliter. The solvent is 2ME and NMP, and the ratio is 9:1. The precursor solution is stirred at room temperature for 18 hours and then filtered. Deposit it on the surface of the hole transport layer through the knife head of the slit coating equipment, set the coating speed to 10mm / s, the injection speed to 0.3ml / min, and the air knife pressure to 0.85bar. At the same time, the air knife is used to form a semi-dry film, and then annealed at 150°C for 30min to form a perovskite film.

[0105] Steps 4-6 are consistent with Steps 4-6 in Example 1.

[0106] Step 7: The active layer is divided by laser scribing. This step is called P2. The line width of P2 is 150 μm. Then, a silver metal electrode with a thickness of 120 nm is prepared on the surface of the copper bath hole blocking layer by thermal evaporation.

[0107] Step 8: Use laser scribing to divide the metal electrodes. This step is called P3, and the line width of P3 is 40um.

[0108] Blank Group 2

[0109] The blank group 2 prepared the perovskite light absorbing layer by referring to the preparation method of Example 2, except that the blank group 2 did not prepare the interface modification layer of step 4.

[0110] Control group 2

[0111] The control group 2 prepared the perovskite light absorbing layer by referring to the preparation method of Example 2. The difference is that when preparing the interface modification layer in step 4, the control group 2 only performed one spin coating and one annealing treatment to obtain the interface modification layer, and did not perform subsequent secondary spin coating and secondary annealing treatment.

[0112] Performance Testing

[0113] 1. The perovskite cells prepared in all the above examples, control group and blank group were placed under a xenon lamp solar simulator (100 mW·cm -2 ), test the battery current density-voltage (JV) curve performance, the results are as follows Figure 3 , Figure 4 , Figure 6 And as shown in Table 1.

[0114] 2. The perovskite cells of Example 1, Control Group 1 and Blank Group 1 were placed under an LED solar simulator (100 mW·cm -2 ), test the maximum power point output curve (MPP), the results are as follows Figure 5 shown.

[0115] Depend on Figure 5It can be seen that the photoelectric efficiency of the unmodified perovskite surface battery in the blank group 1 is 80% of the initial efficiency after 18 hours, and the output fluctuates greatly between the 8th and 9th hours, indicating that the battery structure is unstable; while the perovskite batteries in the control group 1 and Example 1 have an efficiency of 100% of the initial efficiency after 18 hours, and the battery structure is relatively stable, indicating that the low-dimensional structure formed by preparing the interface modification layer on the surface of the perovskite light-absorbing layer of the perovskite battery in the embodiment can effectively inhibit ion migration and improve the stability of the battery device; compared with the control group 1, the maximum power point output curve of Example 1 is smoother, indicating that the low-dimensional structure formed after the two perovskite surface modifications is more stable and the carrier extraction is smoother.

[0116] Table 1

[0117]

[0118]

[0119] As can be seen from Table 1, in Example 1 and Example 2, three functional molecules are mixed to obtain a post-treatment solution, and the interface modification layer is prepared by combining two post-treatment methods, which deepens the action depth of the material in the post-treatment solution in the perovskite light-absorbing layer, increases the concentration of the energy level regulation molecules on the surface of the perovskite, and realizes the gradual increase of the gradient change of the functional molecules from the perovskite bulk phase to the surface, forming a gradient energy level structure that is beneficial to carrier extraction, thereby improving the extraction of carriers and the built-in field of the battery, and significantly improving the efficiency of the perovskite battery, with efficiencies of 23.892% and 18.442%, respectively.

[0120] No interface modification layer was prepared on the surface of the perovskite light-absorbing layer of blank group 1 and blank group 2, and the photoelectric efficiency decreased to 21.001% and 17.487%, respectively.

[0121] The cells of control group 1 and control group 2 were prepared with interface modification layers, but only subjected to one spin coating annealing treatment without further treatment of the perovskite light absorbing layer. Their photoelectric conversion efficiencies were 23.630% and 18.073%, respectively, which were lower than those of example 1 and example 2, respectively.

[0122] Comparative Examples 1-3 are single molecule modifications of the perovskite surface: compared with the blank group, the FACl modification in Comparative Example 1 mainly improves the filling factor, the PEAI molecule in Comparative Example 2 improves both the open circuit voltage and the filling factor, and the PI molecule in Comparative Example 3 has the most obvious effect on improving the open circuit voltage.

[0123] Comparative Examples 4-6 are two molecules modifying the perovskite surface: relative to blank group 1, the performance of the perovskite surface modified by two molecules is uniformly improved, but not as good as the three-molecule post-treatment effect of Example 1 and control group 1.

[0124] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a perovskite battery, characterized in that: The following steps are involved: The post-treatment solution is added dropwise onto the surface of the perovskite light-absorbing layer, and a spin coating process is performed at least twice, and an annealing process is performed after each spin coating process to obtain an interface modification layer; The post-treatment solution includes A-site small molecules, A-site macromolecules and energy level modification molecules; The A-site small molecule includes MA + , FA + DMA + At least one of the following; The A-position macromolecule includes an aromatic amine halide salt; The energy level modifying molecules include diamine halide salts.

2. The method for preparing a perovskite battery according to claim 1, characterized in that: The aromatic hydrocarbon amine halide salt includes phenylethylamine hydroiodide; and / or, the diamine halide salt includes piperazine hydroiodide.

3. The method for preparing a perovskite battery according to claim 1, characterized in that: The molar concentration of the A-site small molecule in the post-treatment solution is 0.01M to 0.1M; and / or, the molar concentration of the A-site macromolecule in the post-treatment solution is 0.01M to 0.1M; And / or, the molar concentration of the energy level modification molecules in the post-treatment solution is 0.01M to 0.1M.

4. The method for preparing a perovskite battery according to claim 1, characterized in that: In the post-treatment solution, the molar ratio of the A-site small molecule, the A-site macromolecule and the energy level modification molecule is (1:1:0.1) to (1:1:0.6).

5. The method for preparing a perovskite battery according to claim 1, characterized in that: The post-treatment solution includes an organic solvent, and the organic solvent includes isopropyl alcohol.

6. The method for preparing a perovskite battery according to claim 1, characterized in that: The rotation speed of the spin coating is 2500rpm~3500rpm; And / or, the spin coating time is 25s to 35s; And / or, the annealing temperature is 95°C to 105°C; And / or, the annealing treatment time is 9 minutes to 11 minutes.

7. The method for preparing a perovskite battery according to claim 1, characterized in that: The thickness of the interface modification layer is 0.1 nm to 3 nm.

8. The method for preparing a perovskite battery according to any one of claims 1 to 7, characterized in that: The preparation method of the perovskite battery comprises the following steps: One spin coating annealing: dripping the post-treatment solution onto the surface of the perovskite light absorbing layer, performing a spin coating process, and performing an annealing process to obtain an initial interface modification layer; Secondary spin coating annealing: dripping the post-treatment solution onto the surface of the initial interface modification layer, performing secondary spin coating treatment, and performing secondary annealing treatment to obtain the interface modification layer.

9. A perovskite battery prepared by the method for preparing a perovskite battery according to any one of claims 1 to 8.

10. The perovskite battery according to claim 9, characterized in that: The perovskite cell comprises, from bottom to top, a transparent electrode, a hole transport layer, a perovskite light absorption layer, the interface modification layer, an electron transport layer and a metal electrode.

Citation Information

Cited By

  • Perovskite battery and preparation method thereof

    CN120417630A